Nanohybrids of RGO nanosheets and 2-dimensional porous Co3O4 nanoflakes working as highly efficient counter electrodes for dye-sensitized solar cells. Issue 43 (24th October 2016) - Du, Feng; Zuo, Xueqin; Yang, Qun; Li, Guang; Ding, Zongling; Wu, Mingzai; Ma, Yongqing; Zhu, Kerong
Abstract : In this paper, nanohybrids (Co3 O4 @RGO) of 2-dimensional (2D) porous Co3 O4 nanoflakes anchored on reduced graphene oxide nanosheets have been fabricated by a facile hydrothermal reduction process. Abstract : In this paper, nanohybrids (Co3 O4 @RGO) of 2-dimensional (2D) porous Co3 O4 nanoflakes anchored on reduced graphene oxide nanosheets have been fabricated by a facile hydrothermal reduction process. The introduction of RGO nanosheets substantially improved the performance of 2D porous Co3 O4 nanoflakes as counter electrodes (CEs) in dye-sensitized solar cells (DSSCs). The DSSCs with this Co3 O4 @RGO CE displayed a power conversion efficiency of 5.79%, which is greatly higher than that of pure Co3 O4 CE (1.2%) or pure RGO CE (2.2%), and even comparable to that of the conventional Pt CE (6.16%). At the same time, with the addition of RGO, the electrochemical stability of Co3 O4 @RGO nanohybrids is also greatly improved. This work gives an idea on how to take the advantage and to avoid the disadvantage of 2D nanoflakes by introducing RGO nanosheets. Meanwhile, the experimental result demonstrates that Co3 O4 @RGO nanohybrids are advanced CEs in DSSCs and may open a window for potential applications in any other related fields.